Revolutionary Thinking in Latif Halmat Poetry - Kwestan Jamal Salam (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This research, under the title “Revolutionary Thinking in Latif Halmat Poetry” aims to analyze and highlight the role of literature and poetry in general and revolutionary poetry in particular. In other words, Kurdish revolutionary poetry written for freedom and independence. Thus, this research underlined the significant role of Latif Halmat in which represented in employing his development thoughts to keep abreast of revolutionary poetry developments. Therefore, this study investigated the stimuli of revolutionary thought, the motivations for writing revolutionary poetry and the excellence of Latif Halmat poetry style. Perhaps, the most significant finding of this research might be the fact that Latif Halmat is one of the poets that dedicated most of his journey to poetry of revolution and resistance. In this context, Latif Halmat in his first poem praises Peshmerga and the martyrs and by that he becomes a revolutionary poet.